Kompetensi Pengadilan Agama Memfasakh Perkawinan atas Dasar Peralihan Agama: Mengapa Yurisprudensi Mahkamah Agung Disimpangi? - Nasution, Muhammad Idris; Syafruddin Syam, Syafruddin (Istinbath : Jurnal Hukum, 2023)
Cancellation or fasakh of marriage due to religious conversion is not included in the family cancellation of marriage as part of the competence of the Religious Courts, but it is implemented through divorce institutions, giving rise to disparities in decisions between fasakh, talak bain and talak raj'i permission. The author found two Supreme Court decisions that canceled and corrected the decisions of two High Religious Courts that canceled a marriage because it was proven that one of the husband and wife had a religious conversion. The Supreme Court is of the opinion that the permit to impose talak raj'i is more appropriate on the grounds according to the posita and petitum of the petition. The Supreme Court consistently applies this rule in its two decisions, but the author finds eleven decisions of the Religious Courts in the following years still impose fasakh if it is proven that one of the married couples is an apostate (out of Islam), even though it is not used as an excuse for divorce and is not requested by the party in the petitum. In this article, the author will examine the legal considerations of eleven Religious Court decisions using an explanatory method and presented qualitatively. The results of the author's study show that the judge's consideration is influenced by the judge's perception of the application of the ultra petita principle with the principle of ex aequo et bono, the judge's perception of the adjudication of fiqh schools and the judge's perception of the independence of judges and compliance with jurisdiction.